2014
DOI: 10.1007/jhep01(2014)107
|View full text |Cite
|
Sign up to set email alerts
|

B s  → K (*)ℓ$ \overline{\nu} $, angular analysis, S-wave contributions and |V ub |

Abstract: We analyse the $ \overline{B}_s^0\to {K^{+}}{l^{-}}\overline{\nu} $ and $ \overline{B}_s^0\to {K^{*+ }}\left( {\to K\pi } \right){\ell^{-}}\overline{\nu} $ decays that are valuable for extracting the CKM matrix element |V ub|. We calculate the differential and integrated partial widths in units of |V ub|2 based on various calculations of hadronic form factors and in particular the latest Lattice QCD calculation of the B … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…Similar conclusions can be reached when considering the figures in [41] with and without the ρ(1450) and ρ(1700) contributions. We note that 5% is of the same order as the S-wave background found in B → ππ ν [42]. other sizeable uncertainties we refrain from adding any further error due to this effect and reemphasise the importance of comparing our result only with the P -wave contribution of the corresponding ππ-pair.…”
Section: Jhep08(2016)098mentioning
confidence: 90%
See 1 more Smart Citation
“…Similar conclusions can be reached when considering the figures in [41] with and without the ρ(1450) and ρ(1700) contributions. We note that 5% is of the same order as the S-wave background found in B → ππ ν [42]. other sizeable uncertainties we refrain from adding any further error due to this effect and reemphasise the importance of comparing our result only with the P -wave contribution of the corresponding ππ-pair.…”
Section: Jhep08(2016)098mentioning
confidence: 90%
“…In ref. [42] (cf. figure 9 of that reference) this effect has been analysed and it has been found that the integrated line-shapes of the S-wave over the interval [m ρ − Γ ρ , m ρ + Γ ρ ] is around 12% of the corresponding P -wave contribution.…”
Section: Jhep08(2016)098mentioning
confidence: 99%
“…To go beyond this approximation requires further studies. A dedicated programme has emerged in recent years to study ππ [10,[24][25][26][27][28][29] and Kπ [30][31][32][33] final states beyond a simple resonance ansatz. LCSR analyses of B → P 1 P 2 form factors require ongoing updates [34,35] by other authors to improve our understanding of the semileptonic processes as well as purely hadronic multi-body B decays [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…At large dipion invariant mass, the QCD factorization is available [2,3], when the invariant mass is small and the hadronic recoil is low, the chiral effective theory of heavy meson is proposed to combine with the dispersion theory [4]. The light-cone sum rules (LCSRs) approach is operative in the regions of large hadronic recoil at low invariant mass, i.e., the S−wave generated B → ππ, Kπ form factors has been calculated [5,6] with the combination of the perturbative theory based on the operator production expansion and the low-energy effective theory inspired by the chiral symmetry, corresponding to the effect from the LCDAs and from the scalar form factors, respectively, and recently the B 0 → π + π 0 form factors has been derived from LCSRs approach with the generalized 2πDAs [7][8][9]. In principle, the low invariant mass in LCSRs approach to deal with B → ππ ν decays goes from the threshold 4m 2 π to the resonance intervals, the previous works follow closely around the threshold while the running on the invariant mass is less attended, but actually this part is indispensable to show the resonance contribution.…”
Section: Introductionmentioning
confidence: 99%